2020
DOI: 10.1002/mana.201800474
|View full text |Cite
|
Sign up to set email alerts
|

Ricci η‐recurrent real hypersurfaces in 2‐dimensional nonflat complex space forms

Abstract: Let M be a Hopf hypersurface in a nonflat complex space form , , of complex dimension two. In this paper, we prove that M has η‐recurrent Ricci operator if and only if it is locally congruent to a homogeneous real hypersurface of type (A) or (B) or a non‐homogeneous real hypersurface with vanishing Hopf principal curvature. This is an extension of main results in [17, 21] for real hypersurfaces of dimension three. By means of this result, we give some new characterizations of Hopf hypersurfaces of type (A) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Thus, combining with Theorem 1.1, we have shown that there do not exist non-Hopf hypersurfaces in with recurrent Ricci tensor. Finally, we noticed that very recently Wang [21] studied Ricci -recurrent real hypersurfaces in .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, combining with Theorem 1.1, we have shown that there do not exist non-Hopf hypersurfaces in with recurrent Ricci tensor. Finally, we noticed that very recently Wang [21] studied Ricci -recurrent real hypersurfaces in .…”
Section: Introductionmentioning
confidence: 99%